1998
DOI: 10.1097/00001888-199811000-00011
|View full text |Cite
|
Sign up to set email alerts
|

On the culture of student abuse in medical school

Abstract: The abuse of students is ingrained in medical education, and has shown little amelioration despite numerous publications and righteous declarations by the academic community over the past decade. The culture of abuse conflicts with the renewed commitments of medical educators and practice professionals to imbue students with a higher degree of professionalism and cultural sensitivity. The authors describe the profiles of student abuse, drawn from recent national surveys of medical students using the AAMC Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
1
14

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 0 publications
7
158
1
14
Order By: Relevance
“…1 It also postulates what it is like to be a learner within a given organization 1 and influences student behavior and the prediction of students' accomplishment, contentment, and success. 2,3 Educational environment studies have shown that there is a high price to be paid for dysfunctional and malfunctioning learning environments, [4][5][6][7][8][9][10] because the educational environment is an indispensable part of the curriculum, affecting the interaction between student, methods, assessment, and educational outcomes. 11 Therefore, evaluating the educational environment, especially in periods of curriculum change, is encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…1 It also postulates what it is like to be a learner within a given organization 1 and influences student behavior and the prediction of students' accomplishment, contentment, and success. 2,3 Educational environment studies have shown that there is a high price to be paid for dysfunctional and malfunctioning learning environments, [4][5][6][7][8][9][10] because the educational environment is an indispensable part of the curriculum, affecting the interaction between student, methods, assessment, and educational outcomes. 11 Therefore, evaluating the educational environment, especially in periods of curriculum change, is encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…After being familiarized to this meager issue of medical graduation, several scales and questionnaire were made to evaluate and identify the ratio of abuse as well as the cause. The Association of American Medical Colleges graduation questionnaires (AAMC GQs-2013) reported student mistreatment rates of 42.1% (Kassebaum and Cutler;1998). Meanwhile, on the other side of the globe (specifically in UK), the General Medical Council (GMC-2012) introduced a new indicator named 'Undermining'.…”
Section: Discussionmentioning
confidence: 99%
“…Se postula incluso que existe una "cultura" del abuso de los estudiantes en las escuelas de Medicina que está vinculada a una sistemática "violación de la dignidad" en los servicios de salud (Uhary, 1994;Kassebaum y Cutler, 1998;Jacobson, 2009). …”
Section: La Producción Del Habitus Médico En La Escuela De Medicinaunclassified